Em suma, somos patéticos : Bufo & Spallanzani, de Rubem Fonseca - Possapp, Yuri Torres (2014)
The tragic and pathos are recurring elements in universal literature, appearing often in counterpoint to a possible rationalism allegedly totalizing, revealing the relative powerlessness of man in relation to the complex reality that surrounds. Ruben Fonseca, respected Brazilian author shows great artistic sensitivity over its contemporary context, namely the post-war world. In the context of a new Generic saturation and systemic nihilism, where axiology is dead, catharsis is no longer possible nor feasible. Due to the seemingly inevitable perplexity that haunts the citizens of this new time, sterile regarding the teleological perspective, tragedy, besides losing its original essence (described by Aristotle), seems to flirt with the comedy itself, pointing to the "ridiculous" that overlaps with the suffering. This dissertation aims to analyze the way that mentioned writer exposes the pathetic and the tragic in his novel Bufo & Spallanzani, first published in 1985, considering the social, political, economic and cultural changes in the world that emerged after the Second World War.